Semi‐Polar InGaN‐Based Green Light‐Emitting Diodes Grown on Silicon. Issue 7 (11th November 2019) - Shen, Shuoheng; Zhao, Xuanming; Yu, Xiang; Zhu, Chenqi; Bai, Jie; Wang, Tao
Abstract : High‐quality semi‐polar (11‐22) GaN is obtained by means of growth on patterned (113) silicon substrates featured with stripy grooves and extra periodic gaps which are perpendicular to the grooves. Ga melting‐back during the GaN growth at a high temperature is eliminated as a result of special patterning design. On‐axis X‐ray rocking curve measurements show that the linewidth is significantly reduced down to 339 arcsec. Photoluminescence (PL) measurements at 10 K show strong GaN band‐edge emission only, meaning that any basal stacking fault‐related emission is not observed. Furthermore, green InGaN/GaN light‐emitting diodes (LEDs) with an emission wavelength of around 530 nm are achieved on the semi‐polar GaN grown on the patterned Si substrates. Excitation power‐dependent PL measurements do not show a shift in wavelength, meaning a significant reduction in polarization‐induced piezoelectric fields. Electroluminescence (EL) measurements exhibit that the output power of the semi‐polar LED increases linearly with increasing injection current. It is worth highlighting that the overgrowth technology on designed patterned (113) silicon is a potential approach to manufacturing high‐performance semi‐polar GaN emitters on Si substrates in a long wavelength region. Abstract : High‐quality semi‐polar (11‐22) GaN is obtained by means of the growth on patterned Si (113) substrates. Due to a special design, the challenging Ga melt‐back issue is completely eliminated. As validation, InGaN/GaN light‐emitting diodes (LEDs) with green emission and 15% internal quantum efficiency are successfully achieved on such high‐quality semi‐polar GaN on Si.